A simple way to make tough diamond/metal laminates - Xuan, Yang; Fromm, Timo; Bruns, Sebastian; Borchardt, Rudolf; Durst, Karsten; Rosiwal, Stefan (Journal of the European Ceramic Society, 2021)
Diamond foils are exceptionally strong yet brittle. One approach to make ceramic foils less susceptible to brittle fracture is to introduce interfaces into the material that provide pathways for crack deﬂection. In this study, we were able to produce strong yet tough diamond/metal laminates (DMLs) from freestanding diamond foils using a brazing process. The mechanical behavior was characterized via three-point bending (3PB) where the laminates exhibit step-like fracture. Crack deﬂection at interfaces induces toughening within the laminates. At approx. 3.0 MJ/m3 diamond/metal laminates exhibit more than twice the fracture energy of monolithic diamond foils while maintaining 90 % stiffness and about 70 % nominal strength. Classical laminate theory (CLT) supports the assessment of the deformation behavior and step-like fracture of diamond/metal laminates. We ﬁnd that the diamond-to-metal interface plays a critical role: it must be strong enough to enable the transfer of shear stress, while being weak enough to deﬂect a crack.<br
Keywords: Diamond foil; Ceramic laminate; Chemical vapor deposition (CVD); Mechanical behavior; Analytical modeling

Bioinspired damage tolerant diamond-metal laminates by alternating CVD and PVD processes - Fromm, Timo; Bruns, Sebastian; Müller, Marie Christin; Fink, Alexander; Borchardt, Rudolf; Rosiwal, Stefan; Durst, Karsten (Materials & Design, 2022)
In this study, we present a novel process to fabricate diamond-metal laminates. By means of successive chemical vapor deposition and physical vapor deposition processes, the lamellar material is deposited layer by layer on silicon wafers. Laminates consisting of two, five and ten layers of diamond were realized. In addition, fabrication of diamond-based, biomimetic brick-and-mortar structures was successful for the first time. For this purpose, diamond layers of a five-layer laminate were structured by laser cutting into hexagonal platelets with diameters of 400 µm and 800 µm. The mechanical behavior was characterized by three-point bending. Mostly spontaneous failure with little crack deflection was observed, indicating a strong diamond-metal interface. At over 1250 MPa, the laminates exhibit nominal strengths that exceed those of other lamellar ceramic-metal composites by at least a factor of two, while fracture energy lies in a medium range. The laminates with segmented diamond layers exhibit damage tolerance.
CRIS-Team Scopus Importer:2021-12-24
Keywords: Biomimetic materials; Ceramic laminates; Chemical vapor deposition (CVD); Diamond foil; Physical vapor deposition (PVD); Toughness

Boron-doped diamond (BDD) as an efficient back contact to thermally grown TiO2 photoelectrodes - Özkan, Selda; Ghanem, Hanadi; Mohajernia, Shiva; Hejazi, Seyedsina; Fromm, Timo; Borchardt, Rudolf; Rosiwal, Stefan; Schmuki, Patrik (ChemElectroChem, 2019)
In the present work, we investigate the efficiency of TiO2 photoelectrode layers on boron-doped diamond foil (BDDF) in comparison with a classic conducting glass (fluorine-doped tin oxide, FTO) back contact. Crystalline thin TiO2 layers were prepared on the substrates by two different methods: (i) deposition of metallic Ti thin films followed by thermal oxidation to form TiO2 (TO-TiO2), (ii) reactive sputter deposition of TiO2 thin films and crystallization of these layers (SP-TiO2). Optimized layers show that TO-TiO2 films on BDDF deliver a significantly higher incident photon to current ifficiency (IPCE) compared to directly sputtered SP-TiO2 layers and these layers on BDDF also outperform FTO as a back contact. We ascribe this beneficial effect of the BDDF back contact to the formation of an intermediate conductive phase of Ti-carbides at the TO-TiO2/BDDF interface.

Novel structuring technique for diamond coatings - Borchardt, Rudolf; Sand, Philipp; Fromm, Timo; Rosiwal, Stefan (Diamond and Related Materials, 2020)
Here we report a novel structuring technique for diamond coatings using a copper masking on a previously deposited diamond layer to epitaxially grow a subsequent diamond layer only at the exposed areas of the mask. An 8 mu m thick copper mask is applied onto the substrate using physical vapor deposition and structured by standard photolithographic methods. Hot filament chemical vapor deposition is used to grow the 14 mu m thick structured diamond layer on the diamond coated silicon wafer. Micro and nano crystallinity of the diamond layers are varied, as well as the doping with boron to verify the applicability of the new structuring method for different kinds of diamond qualities. It is shown that four-inch wafers can be fully structured with this high temperature masking technique and the resolution was mostly affected by the quality of the printed mask used for the photolithographic structuring of the copper mask. This diamond structuring method could pave the way for diamond being used in electronics or adding additional functionalities to diamond coated tools.
CRIS-Team WoS Importer:2021-01-08

Thermoelektrische und photovoltaische Energiewandler auf Basis von CVD-Diamant- und Carbonnanowallschichten - Borchardt, Rudolf (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2025)

World's First Thermoelectric Generator Made of Tailored Carbon Allotropes - Borchardt, Rudolf; Fromm, Timo; Haase, Armin; Fecher, Jonas; Rosiwal, Stefan (Advanced Engineering Materials, 2020)
Carbon and carbon-based compounds are today's mostly used sources of energy. By burning them, their chemically stored energy can be transformed to mechanical energy and further on to electrical energy. These transformation steps entail huge thermal losses. Thermoelectric generators (TEGs) are devices that allow the direct conversion of thermal gradients into electrical energy through a smart combination of n- and p-conducting materials and are therefore an appealing approach to tackle thermal losses. However, the materials in today's TEGs, e.g., Bi2Te3, show limited thermal stability and often are toxic or not abundantly available which only allow for niche applications like military and aerospace equipment. Herein, the fabrication of the first, fully functional all-carbon TEG is shown. The used carbon materials, made by chemical vapor deposition (CVD) processes, are both, nontoxic and abundant, and potentially paves the way for the large-scale use of TEGs. Not only the thermal losses of conventional combustion processes but also thermal gradients established by solar thermal systems are potential fields of application. The assay is anticipated to spark further interest in carbon-based thermoelectric materials. Such materials can be produced on a large scale and combined to a fully functional thermoelectric device.
CRIS-Team WoS Importer:2020-05-19